Effect of Inhaled Magnesium Sulphate on Bronchodilating Response, Levels of Substance P and Clinical Improvement of Acute Exacerbations COPD Patients - Prima Karita Sari; Suradi Suradi; Jatu Aphridasari (Jurnal Respirologi Indonesia, 2018)
Background: Inhaled magnesium sulphate has a bronchodilator and antiinflammatory effect by block the calcium channels and inhibiting substance P. This study aimed to analyze the effect of magnesium sulfate inhalation on bronchodilator response, substance P levels, and clinical improvement on AECOPD patients. Methods: A quasi-experimental clinical trial, pre-test and post-test design with 34 acute exacerbation of COPD patients who are hospitalized in emergency room on Dr. Moewardi Hospital, Surakarta and Ario Wirawan Hospital, Salatiga on March-April 2017 used consecutive sampling. The independent variable is inhaled magnesium sulphate dose of 150 mg 3 times every 20 minutes when the patients was admitted in emergency room, while the dependent variables are peak expiratory flow rate, the plasma levels of substance P and CAT score acute exacerbation of COPD patients. Results: There was a significant difference (P=0.009) decrease of PEFR value of treatment group (111.76±12.37) compared to control group (141.18±24.21). There was a significant difference (P=0.0001) decrease in CAT score of treatment group (-14.88±1.75) compared to control group (-9.00±1.17). There was a significant difference (P=0.0001) treatment group (-1305.92±417.91) than control group (-355.95±206.25). Conclucions: The addition of MgSO4 inhalation of 150 mg during exacerbation increased PEFR, decreased the level of P substance, and decreased the CAT score with statistically significant results. (J Respir Indo 2018; 38(1): 16-23)